Evaluating lithium diffusion mechanisms in the complex spinel Li2NiGe3O8. Issue 41 (11th October 2019) - Martin, Daniel Z. C.; Haworth, Abby R.; Schmidt, Whitney L.; Baker, Peter J.; Boston, Rebecca; Johnston, Karen E.; Reeves-McLaren, Nik
Abstract : Li + -ion diffusion in the all-solid-state battery electrolyte candidate material Li2 NiGe3 O8 was investigated and D Li = 3.89 × 10 −12 cm 2 s −1 calculated. Abstract : Lithium-ion diffusion mechanisms in the complex spinel Li2 NiGe3 O8 have been investigated using solid-state NMR, impedance, and muon spectroscopies. Partial occupancy of migratory interstitial 12 d sites is shown to occur at lower temperatures than previously reported. Bulk activation energies for Li + ion hopping range from 0.43 ± 0.03 eV for powdered samples to 0.53 ± 0.01 eV for samples sintered at 950 °C for 24 h, due to the loss of Li during sintering at elevated temperatures. A lithium diffusion coefficient of 3.89 × 10 −12 cm 2 s −1 was calculated from muon spectroscopy data for Li2 NiGe3 O8 at 300 K.